Efektivitas Pemungutan Pajak Hotel dan Kontribusinya Terhadap Pendapatan Asli Daerah (PAD) Kab. Serang 2015-2020 - Khatulistiwa, Dimas Noto Jagat; Sukiyaningsih, Tri Wahyuni (Institut Ilmu Sosial dan Manajemen STIAMI, 2023)
This study aims to determine the level of effectiveness of hotel tax collection and its contribution to regional original income 2015 - 2020 seen from the target and realization. This type of research and research approach uses descriptive qualitative. Types and Sources of data This research uses primary and secondary data from research sites and library research on the internet or similar research. The population and sample used in this study are hotel taxes from a hotel and the sample is hotel tax Serang Regency 2015 - 2020. Data collection techniques use qualitative descriptive. This study was conducted to determine how effective the collection of hotel taxes in the government is and how big the contribution of hotel taxes is to local revenue. Based on the results of the study, it can be concluded that the effectiveness of hotel tax collection is very effective but still low in terms of contribution to local revenue in Serang Regency